2012
DOI: 10.1038/onc.2012.81
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibitors suppress mutant p53 transcription via histone deacetylase 8

Abstract: Mutation of the p53 gene is the most common genetic alteration in human cancer and contributes to malignant process by enhancing transformed properties of cells and resistance to anticancer therapy. Mutant p53 is often highly expressed in tumor cells at least in part due to its increased half-life. However, whether mutant p53 expression is regulated by other mechanisms in tumors is unclear. Here, we found that histone deacetylase inhibitors suppress both wild-type and mutant p53 transcription in time- and dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
103
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(108 citation statements)
references
References 51 publications
5
103
0
Order By: Relevance
“…Such a discriminatory feature appears to be encoded in the expression of the wild-type versus mutant forms of the tumor suppressor protein p53 in the above cell lines, respectively. Yan et al (17) recently demonstrated that the transcription of both the wildtype and the mutant p53 genes are regulated via HDAC8 in various human cancer cells (17). In addition, when the cancer cells express the mutant forms of HDAC8 (exhibiting lower catalytic activity), the up-regulation of p53 is obviated.…”
Section: Table 3 Kinetic Parameters For the Hdac8-catalyzed Reaction mentioning
confidence: 99%
See 2 more Smart Citations
“…Such a discriminatory feature appears to be encoded in the expression of the wild-type versus mutant forms of the tumor suppressor protein p53 in the above cell lines, respectively. Yan et al (17) recently demonstrated that the transcription of both the wildtype and the mutant p53 genes are regulated via HDAC8 in various human cancer cells (17). In addition, when the cancer cells express the mutant forms of HDAC8 (exhibiting lower catalytic activity), the up-regulation of p53 is obviated.…”
Section: Table 3 Kinetic Parameters For the Hdac8-catalyzed Reaction mentioning
confidence: 99%
“…Considering the fact that HDAC8 enhances the expression of p53 (17), the treatment of cancers by HDAC inhibitors should be used with caution. This is primarily because the inhibition of HDAC8 (by SAHA and other pan-HDAC inhibitors) would suppress the up-regulation of the wild-type p53 gene, obviating the tumor-protective effects of p53 and p21.…”
Section: Table 3 Kinetic Parameters For the Hdac8-catalyzed Reaction mentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that other HDACs are involved in regulating TAp73 transcription, although the underlying mechanism is not clear. Recently, HDAC8, a class I HDAC, was found to regulate p53 transcription via transcription factor HoxA5 (45). In addition, the activity of E2F1, a known p73 regulator, is found to be regulated by HDACI (61).…”
Section: Volume 288 • Number 11 • March 15 2013mentioning
confidence: 99%
“…For example, HDAC1 deacetylates p53 and affect its transcriptional activity (42,43), whereas HDAC2 modulates the ability of p53 to bind DNA and p53-dependent transcription (44). Additionally, p53 transcription is found to be regulated by HDAC8 via HoxA5, whereas the protein stability of mutant p53 is found to be regulated by HDAC6-Hsp90 chaperone (45,46). Furthermore, ⌬Np63 transcription is found to be regulated by HDAC2 via Dec1 (47).…”
mentioning
confidence: 99%